2021
DOI: 10.21203/rs.3.rs-294775/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Acceptance of Coronavirus Disease-2019 (COVID-19) Vaccine Among Lebanese Health Care Workers Using Health Belief Model

Abstract: Background: Since Health care workers (HCWs) are at high occupational risk for COVID-19, they are prioritized for immunization. This study aims to assess the acceptance rate of COVID-19 vaccine among HCWs and to identify its determinants.Methodology: A web-based cross-sectional study was conducted over the period extending from 10 to 31 December 2020 among Lebanese HCWs. The Health Belief Model (HBM) was used as theoretical framework. Descriptive statistics were reported using frequency with percentages for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 24 publications
2
48
2
Order By: Relevance
“…79 Health workers in Egypt stated that they would not be influenced by celebrities and leaders advocating the COVID-19 vaccine (69%), 71 and in Lebanon, health workers who had been advised by family members to vaccinate were less likely to accept the vaccine. 77 These are important findings, which should be explored further in other studies.…”
Section: The Communication Environmentmentioning
confidence: 83%
See 3 more Smart Citations
“…79 Health workers in Egypt stated that they would not be influenced by celebrities and leaders advocating the COVID-19 vaccine (69%), 71 and in Lebanon, health workers who had been advised by family members to vaccinate were less likely to accept the vaccine. 77 These are important findings, which should be explored further in other studies.…”
Section: The Communication Environmentmentioning
confidence: 83%
“…71 In Lebanon, health authorities' or health facilities' recommendation to vaccinate by was positively linked to vaccine acceptance and stood out as one of the most important cues for vaccination. 77 A framing experiment in Lebanon found that health workers responded better to information shared by health peers or experts than by religious leaders or celebrities. 58 Health workers may contribute to lower vaccine acceptance in some settings.…”
Section: The Communication Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a previous study, the average proportion of people accepted to be vaccinated is 58% [31]. Therefore, an approximate value of 65% was selected for the calculation of sample size.…”
Section: Sample Size Calculationmentioning
confidence: 99%